Μια εμπειρική αξιολόγηση της επίδοσης των Ελλήνων διαχειριστών αμοιβαίων κεφαλαίων - Φίλιππας, Νικόλαος (SPOUDAI Journal of Economics and Business, 2001)
During the last years the mutual funds industry has experienced explosive growth, not only worldwide but in Greece also. This growth can be attributed to the unique benefits that mutual funds offer to individual investors. As a result of this widely documented trend, the performance of portfolio managers has become an increasingly important focus among financial analysts. This paper is unique in evaluating Greek mutual fund managers in terms of «market timing» and «selectivity» performance using new methodology. It should be noted that since the official General Index does not include dividends, a new index named Total Performance Index, constructed by us, is employed into the analysis. The empirical results do not reveal any ability of the fund managers to time the market correctly or select undervalued securities, irrespectively of how the returns of the index are calculated. JEL Classification: G14